(untitled) (BSAA arte, 2020)
From the 1890s, 15th and 16th century Flemish painting rediscovery generated a large-scale production of Flemish Primitives forgeries. While some of these are made using a modern support, others are paintings abusively restored. A certain number of these fakes found their way into Spanish collections, and even famous authors such as Chandler Post, Jacques Lavalleye and Elisa Bermejo believed them to be genuine Flemish or Hispano-Flemish works. Amongst the newly detected forgeries investigated in this contribution, some can be ascribed to the Belgian restorer and forger Joseph Van der Veken, others to the mysterious ’Valls Marín Forger’.